Design, Synthesis, Enzymatic Inhibition, and Antioxidant Activity of New 4-Phenylpiperazin-phenoxy-1,2,3-triazol-acetamide Derivatives as Tyrosinase Inhibitors - Alaeddini, AmirHossein; Karimian, Somaye; Noori, Milad; Dastyafteh, Navid; Mohammadi-Khanaposhtani, Maryam; Ghomi, Minoo Khalili; Bararjanian, Morteza; Iraji, Aida; Javanshir, Shahrzad; Larijani, Bagher; Ranjbar, Parviz Rashidi; Mahdavi, Mohammad (Synlett, 2025)
In this study, a 4-phenylpiperazin-phenoxy-1,2,3-triazol-acetamide scaffold was designed as a potent skeleton against tyrosinase by molecular hybridization theory. After that, nineteen derivatives of this scaffold were synthesized and evaluated in vitro and in silico against tyrosinase and the obtained data were compared with kojic acid as a strong tyrosinase inhibitor. Among the nineteen synthesized derivatives, four were more potent than kojic acid against mushroom tyrosinase. In this regard, one compound was around twofold more potent than kojic acid and was a competitive inhibitor for tyrosinase. In silico molecular modeling studies of the interactions of it and kojic acid with the active site of tyrosinase showed that this compound has more favorable binding energy than kojic acid. Moreover, a dynamics study of this compound showed that this compound forms a stable complex with tyrosinase.
Keywords: 1,2,3-triazole; 4-phenylpiperazine; tyrosinase; molecular modeling; dynamics